NEETs - One social group, many profiles: A proposed descriptive profiling of psychological dimensions - Ellena, A. M.; Marzana, D.; Marta, E.; Rosina, A.; Simões, F.; Pozzi, M. (Rivista Internazionale di Scienze Sociali, 2023)
The not in employment, education or training (NEET) category is now widely used in many con- texts to refer to young people who are not studying, not working and not in training. However, this category is very broad and its delimitation does not always allow for successful interventions and policies. This paper aims to psychologically profile the diverse groups of NEETs (as proposed by Eurofound) in order to provide qualitative aspects in terms of different variables. This research employs data collected by the Osservatorio Giovani of the Istituto Toniolo di Studi Superiori (Mi- lan, Italy) for a sample of 1257 NEETs. Chi-squared and ANOVA tests were conducted on demo- graphic, psychological and soft-skill variables. The results consist of an accurate description of each NEET category that takes into account these variables.